A Comparison of CNTFET Models through the Design of a SRAM Cell. (14th September 2016) - Marani, R.; Perri, A. G.
Abstract : In this paper we present a comparison of CNTFET models through the design of a SRAM cell, in order to identify the one more easily implementable in simulation software. In particular we consider two models, the first, already proposed by us, and the Stanford-Source Virtual Carbon Nanotube Field-Effect Transistor model (VS-CNFET). The simulation results of the design of a SRAM cell structure in CNTFET technology, by using the two models, are shown highlighting the comparison in terms of performance, power dissipation and stability.